A study of high lift aerodynamic devices on commercial aircrafts - Swamy Naidu Venkata Neigapula; Satya Prasad Maddula; Vasishta Bhargava Nukala (Aviation, 2020)
Aerodynamic performance of aircraft wings vary with flight path conditions and depend on efficiency of high lift systems. In this work, a study on high lift devices and mechanisms that aim to increase maximum lift coefficient and reduce drag on commercial aircraft wings is discussed. Typically, such extensions are provided to main airfoil along span wise direction of wing and can increase lift coefficient by more than 100% during operation. Increasing the no of trailing edge flaps in chord wise direction could result in 100% increment in lift coefficient at a given angle of attack but leading edge slats improve lift by delaying the flow separation near stall angle of attack. Different combinations of trailing edge flaps used by Airbus, Boeing and McDonnel Douglas manufacturers are explained along with kinematic mechanisms to deploy them. The surface pressure distribution for 30P30N airfoil is evaluated using 2D vortex panel method and effects of chord wise boundary layer flow transitions on aerodynamic lift generation is discussed. The results showed better agreements with experiment data for high Reynolds number (9 million) flow conditions near stall angle of attack.